Relationship of Motivational Techniques used by Secondary School Teachers with Academic Performance of Students in District Bagh AJ&K - Ms. Sanam Saleem; Dr. Fouzia Tabassum; Dr. Muhammad Asghar Ali, (Dialogue Social Science Review (DSSR), 2025)
The study was carried out with the purpose to find out the relationship of motivational techniques used by teacher with academic performance of students at secondary level. The objectives of the study were to find out the motivational techniques used by teacher in classroom at secondary level and to find out the relationship between motivational techniques used by teacher and performance of students. Descriptive research design was used for this study. The method adopted for the research study was a survey method. The set of individual, item or data from which a statistical sample is taken is called population. There were 87 secondary schools (47 male and 40 Female) in district Bagh. The total Number of teacher teaching at secondary level was 226 (147 male and 79 female) the data of population was confirmed by DEO Offices male and Female Bagh. Researcher prepared a questionnaire using five points likert scale after reviewing the literature. Questionnaire was made for the teacher only. The questionnaire was administered to the respondents. The information from the respondents were collected and recorded by the researcher to avoid any kind of discrepancies .The researcher collected data by herself. The data collected was tabulated analyzed and interpreted in the light of the objectives of the study. Frequency, percentage and Pearson correlation was used to analyze the data collected from the respondents. The study showed a positive and significant relationship of motivation al techniques used by teacher with students’ academic performance. It is recommended that teachers may use motivational techniques to enhance academic performance. Key words: Motivation techniques, Academic Performance, Secondary Schools